2009
DOI: 10.1542/peds.2008-1292
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Early Weight Gain to Childhood Overweight and Metabolic Health: A Longitudinal Study (EarlyBird 36)

Abstract: Most excess weight before puberty is gained before 5 years of age. Weight at 5 years of age bears little relation to birth weight but closely predicts weight at 9 years of age. Single measures of current weight are predictive of metabolic health, whereas weight gain within a specific period adds little. A single measure of weight at 5 years of age provides a pointer to future health for the individual. If metabolic status at 9 years of age means future risk, diabetes/cardiovascular prevention strategies might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
200
3
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(216 citation statements)
references
References 42 publications
7
200
3
6
Order By: Relevance
“…The wide divergence in offspring BMI-SDS according to category of parental BMI already present at 5 years, but lack of difference at birth, suggests an early post-natal (but not gestational) influence, and we have documented elsewhere that over 90% of the weight centiles crossed before puberty by contemporary girls (470% in boys) are crossed before the age of 5 years. 22 Others have suggested that the first few months of life may be crucial. 23 The implications may be important, where so much emphasis is placed on school physical education, school dinners, school transport and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The wide divergence in offspring BMI-SDS according to category of parental BMI already present at 5 years, but lack of difference at birth, suggests an early post-natal (but not gestational) influence, and we have documented elsewhere that over 90% of the weight centiles crossed before puberty by contemporary girls (470% in boys) are crossed before the age of 5 years. 22 Others have suggested that the first few months of life may be crucial. 23 The implications may be important, where so much emphasis is placed on school physical education, school dinners, school transport and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The short-and long-term health consequences of elevated BMI in childhood and adolescence remain unclear. While some prospective studies suggest that excess weight gain during these developing years is directly associated with adverse future health outcomes, including incidence of type 2 diabetes (T2D) (4,5) , CVD (6,7) and some cancers (8,9) , others disagree (10)(11)(12) . Studies that fail to show a relationship between childhood weight and disease outcome in adulthood have suggested that significant relationships dissipate when adjusted for adult BMI (12) .…”
mentioning
confidence: 99%
“…One British study that generated an enormous amount of media interest was analysis of the EarlyBird cohort by Gardner et al (2009). This study examined weight gain (defined as an increase in weight z-score [z-scores are age-and sexstandardised measurements, so an increase in weight z-score means an increase in weight given what would be expected from a child's age and sex]) between birth, five years, and nine years in a cohort of 233 children from the south-west of England.…”
Section: When Do Children Become Overweight or Obese?mentioning
confidence: 99%
“…They also suggest that potential risk factors in school-aged children should be de-emphasised, stating "given the pattern of weight gain reported here, the contribution to childhood obesity by computers, school meals, (lack of) sports clubs, (absence of) school playing fields, and the 'school-run' (all of which are vilified regularly by the media) might be questioned". This analysis of the EarlyBird study, however, included only 233 children with weight as the only measure of adiposity, and measurements at just three ages -birth, five and nine years (Gardner et al 2009). …”
Section: When Do Children Become Overweight or Obese?mentioning
confidence: 99%
See 1 more Smart Citation